2020
DOI: 10.1177/0194599820955180
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Obesity on Endoscopic Sinus Surgery Postoperative Complications: An Analysis of the NSQIP Database

Abstract: Objective To evaluate the influence of body mass index on postoperative adverse events in adult patients undergoing endoscopic sinus surgery. Study Design Retrospective cohort study. Setting Database of the American College of Surgeons NSQIP (National Surgical Quality Improvement Program) from 2006 to 2018. Methods The NSQIP database was queried for adult patients undergoing endoscopic sinus surgery. The total sample (N = 1546) was stratified by nonobese (18.5 kg/m2≤ body mass index <30 kg/m2) and obese (≥3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 34 publications
(80 reference statements)
1
25
0
Order By: Relevance
“…20,21 Wardlow et al utilized the NSQIP database to examine the implications of obesity on postoperative adverse events (e.g., unplanned admission, unplanned reoperation, bleeding) of ESS. 11 Interestingly, they found that elevated body mass index (≥30) was a significant predictor of reduced surgical complications after adjusting for other demographic factors and comorbidities (OR: 0.740; 95% CI, 0.566-0.968, P = .028). They hypothesized that overweight and mildly obese patients have higher metabolic states and nutritional reserves that allow them to withstand inflammatory stressors such as surgical intervention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…20,21 Wardlow et al utilized the NSQIP database to examine the implications of obesity on postoperative adverse events (e.g., unplanned admission, unplanned reoperation, bleeding) of ESS. 11 Interestingly, they found that elevated body mass index (≥30) was a significant predictor of reduced surgical complications after adjusting for other demographic factors and comorbidities (OR: 0.740; 95% CI, 0.566-0.968, P = .028). They hypothesized that overweight and mildly obese patients have higher metabolic states and nutritional reserves that allow them to withstand inflammatory stressors such as surgical intervention.…”
Section: Discussionmentioning
confidence: 97%
“…9,10 Although acute complications are typically rare, with frequencies ranging from 0% to 3% in prior studies, their incidence may be greater in patients with certain predispositions, such as obesity, uncontrolled hypertension, and poorly controlled asthma. 5,11 Surgeons would benefit from a better understanding of preoperative risk factors, as this would aid in reducing the incidence of admission after planned outpatient procedures. 12 Our study utilized the American College of Surgeons' National Surgical Quality Improvement Project (NSQIP), a large national database that collects prospective patient information from a wide assortment of surgical cases.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative complications were categorized as surgical or medical complications, consistent with previous NSQIP studies in the literature. 20,21 Surgical complications consisted of superficial surgical site infection (SSI), deep SSI, organ/space SSI, wound disruption, and blood transfusion within 72 hours. Medical complications consisted of pneumonia, unplanned reintubation, urinary tract infection, deep vein thrombosis, renal insufficiency, pulmonary embolism, ventilator >48 hours, acute renal failure, cerebrovascular accident with neurological deficit, cardiac arrest requiring cardiopulmonary resuscitation, myocardial infarction, sepsis, or septic shock.…”
Section: Methodsmentioning
confidence: 99%
“…Complications were categorized as surgical or medical according to previous NSQIP studies. 3 ASA classification was categorized as 1-2, 3, and 4-5. Patients were also divided into three groups according to age (18-49, 50-64, ≥65 years).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were divided into three mFI groups (0, 1, 2–5). Complications were categorized as surgical or medical according to previous NSQIP studies 3 . ASA classification was categorized as 1–2, 3, and 4–5.…”
Section: Methodsmentioning
confidence: 99%